Traditional Climate Responsible Solutions in Iranian Ancient Architecture in Humid Region - Elham Mehrinejad Khotbehsara; Fereshte Purshaban; Sara Noormousavi Nasab; Abdollah Baghaei Daemei; Pegah Eghbal Yakhdani; Ramin Vali (Civil Engineering Journal, 2018)
The climatically compatible design is one of the closest ways getting the optimum use of renewable sources of energy since consideration to climatic conditions is the main concern in sustainability. Occupants suffer from this uncomfortable situation due to the overheating indoor high temperature. This region is located north of Iran, is influenced by humid climate conditions. Adaptation to climate condition in the vernacular architecture of west of Guilan is the main reason of using all these solutions to use the environmental potential for providing comfort for its occupants, which are the main purposes of sustainable development. The research question is how the Guilan’s historical architecture has been able to answer the weather conditions. In this research was performed by analysing appropriate climatic solutions in the vernacular architecture of west of Guilan. The methodology based on a Qualitative–interpretative approach was applied. Their location, formation and different functions are investigated. According to this issue, porches and balconies provide best solutions for weather balance conditions in summer and winter and climate comfort.